Efek Penambahan Nanokitosan 1% Kedalam Berbagai Konsentrasi Ekstrak Kulit Kelengkeng Streptococcus Mutans - Titania Aurely Tandra; Sabrina Khairunissa; Mellisa Sim; Florenly Florenly (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Longan skin (Dimocarpus longan Lour) contains flavonoid compounds, glycosides, saponins, and tannins, so it has an antibacterial capacity. 1% Nanocitosan mixed into plant extracts can increase the inhibitory growth of bacteria in the oral cavity. This study aims to compare the effectiveness of longan skin extract (Dimocarpus longan Lour) added 1% nano chitosan in inhibiting Streptococcusmutans at various concentrations, namely 40%, 60%, and 80%. Longan skin extract is made by maceration method and made with a concentration of 40%, 60%, and 80%. Whereas 1% of nano chitosan is made by the ionic glass method. The two ingredients were mixed in a ratio of 1: 1, and the effectiveness of inhibition was tested by the disk diffusion method. The results showed the mean and standard deviation of longan skin extract at concentrations of 40%, 60% and 80% with 1% nano chitosan was 6.86 ± 0.471 mm; 7.62 ± 0.533 mm and 8.53 ± 0.395 mm. Inhibition with a diameter> 7 mm indicates medium-strength antibacterial. The Shapiro-Wilk test proves that the data are normally distributed. Statistical analysis with one-way Analysis of Variance (ANOVA) showed longan skin extract (Dimocarpus longan Lour) mixed with 1% nano chitosan most effective in inhibiting Streptococcus mutans at 80% concentration, where p = 0,000 (0 <0.05). This is due to an increase in the concentration of phytochemical compounds